Curahan tenaga kerja dan faktor-faktor yang mempengaruhi pemeliharaan entok di Distrik Wanggar Kabupaten Nabire : Outpouring of labor and factors affecting duck cultivation in Wanggar District, Nabire Regency - Mawarni, Nafi’ah; Murwanto, Agustinus; Pakage, Stepanus; Baaka, Alnita; Nuhuyanan, Lambertus E. (Fakultas Peternakan Universitas Papua, 2024)
Abstract This study aims to determine the amount of labor outpouring of duck farming and determine the effect of the number of livestock ownership, cage area, area for raising ducks freely, livestock experience on the outpouring of entok farming labor. This research was conducted in Wanggar District, Nabire Regency on July 4 – 24, 2022. The method used in this study is the descriptive method. The subject of this study was an entok breeder in Wanggar District, the sample of respondents studied was 52 breeders. The data analysis used is descriptive statistical analysis and to find out the comparison, multiple linear analysis is used with the stepwise method. The results of this study were obtained: (1) The outpouring of entok maintenance labor in Wanggar District has an average of 29.04 HOK/breeder/year with a standard deviation of 10.62 HOK/breeder/year. (2) The number of livestock ownership, the area of the pen, the area of the barn, and the experience of raising livestock together have no effect on the outpouring of labor. (3) The results of the stepwise regression analysis are only the number of livestock ownership which has a significant effect on the outpouring of labor. Every increase in the number of duck will increase the outpouring of labor by 0.1479 HOK / year. Keywords: Cage area; Farming ducks; Farming experience; Number of Livestock Ownership; Outpouring of Labor. Abstrak Penelitian ini bertujuan untuk mengetahui besarnya curahan tenaga kerja pemeliharaan entok dan mengetahui pengaruh jumlah kepemilikan ternak, luas kandang, luas tempat umbaran, pengalaman beternak terhadap curahan tenaga kerja pemeliharaan entok. Penelitian ini dilaksanakan di Distrik Wanggar Kabupaten Nabire pada tanggal 4 – 24 Juli 2022. Metode yang digunakan dalam penelitian ini adalah metode deskriptif. Subjek penelitian ini adalah peternak entok di Distrik Wanggar, Sampel responden yang diteliti sebanyak 52 peternak. Analisis data yang digunakan adalah analisis statistika deskriptif dan untuk mengetahui perbandingan digunakan analisis linear berganda dengan metode stepwise. Hasil penelitian ini diperoleh: (1) Curahan tenaga kerja pemeliharaan entok di Distrik Wanggar memiliki rata-rata sebesar 29,04 HOK/peternak/tahun dengan standar deviasi sebesar 10,62 HOK/peternak/tahun. (2) Jumlah kepemilikan ternak, luas kandang, luas tempat umbaran, dan pengalaman beternak secara bersama-sama tidak berpengaruh terhadap curahan tenaga kerja. (3) Hasil analisis regresi stepwise hanya jumlah kepemilikan ternak yang memiliki pengaruh nyata terhadap curahan tenaga kerja. Setiap kenaikan jumlah ternak entok akan menambah curahan tenaga kerja sebesar 0.1479 HOK/tahun.. Kata kunci: Curahan Tenaga Kerja; Jumlah Kepemilikan Ternak; Luas kandang, Pemeliharaan Entok; Pengalaman beternak